Zasada humanitaryzmu w krajowych i międzynarodowych standardach prawa penitencjarnego Krzysztof Chmielewski, Maciej Pająk - Chmielewski, Krzysztof; Pająk, Maciej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
This paper points out the most important international and internal acts which refer to prisoners’ rights in the context of the principle of humanity. The first part describes the Polish situation with regards to constitutional principles of human dignity and freedom from unfair treatment. The second part focuses on international standards, and is divided into two groups: UN standards and European standards. This leads to the conclusions contained in the third section about respecting these articles in contemporary Polish penitentiary law and prisons.